Mapping the Research Landscape of Factors Affecting Earnings Management: A Bibliometric Study - Indrian Supheni; Sri Murni; Ari Kuncara Widagdo; Rahmawati Rahmawati; Eko Arief Sudaryono (Journal of Law and Bibliometrics Studies, 2026)
Objective: Earnings management is a practice that remains a subject of debate in accounting because it can be viewed as a financial performance management strategy or as an action that may mislead stakeholders. This study aims to identify and synthesize factors influencing earnings management practices based on published research findings. Method: A Systematic Literature Review (SLR) was used, with planning, conducting, and reporting stages. Data were obtained through a search for articles using the keyword "earnings management" in the databases Google Scholar, Elsevier, Emerald, Open Knowledge Maps, and ResearchGate during the period 2020–2024. Of the 713 articles found, 17 met the inclusion criteria and were subjected to further analysis. Results: The research results show that nine main factors influence earnings management: board of commissioners, leverage, dividend payments, profitability, company size, liquidity, good corporate governance, company age, and sales growth. Furthermore, most of the research was conducted on manufacturing companies listed on the Indonesia Stock Exchange. Novelty: The findings also indicate a variation in research results regarding the influence of each factor on earnings management practices. The novelty of this research lies in presenting a comprehensive synthesis of the factors influencing earnings management and mapping research trends, which can serve as a basis for developing research agendas and decision-making in the fields of accounting and corporate governance.